Pelaksanaan Kegiatan Pemantau Pemilu Pada Lokasi TPS Kelurahan Buliang & Kelurahan Bukit Tempayan - Lisa Teo; Kellyn Kellyn; Willsen Austin; Tracy Tay; Hengky Lau; Dicky Ananta Huns; Lyvia Lyvia; Paolo Tandiono; Averina Zoraya; Sheren Angelina; Carrolyn Febrianti; Fenny Royentricia; Celvian Celvian; Indah Waty; Jollyn Jollyn; Ronaldo Calvin Pua; Arwin Samuel; M.Arif Rivady; Vito Vito; Hennie Selviani; Hendro Murtiono; Fitriana Aidnilla Sinambela; Agustianto Agustianto (National Conference for Community Service Project (NaCosPro), 2023)
The coklit process (voter data collection) is an important process in a democratic system. Elections are a means of implementing people's sovereignty, general, honest, and fair. Coklit can improve the preliminary data collection process. In this case, Batam International University students carry out and supervise the implementation of this election monitoring activity in order to increase public participation for the 2024 elections. During the implementation there were a number of discrepancies and obstacles found during the implementation of the activity so that it could not be carried out, namely KTPs of residents who came from outside Batam, found coklit stickers on residents' homes, residents had not been visited by officers before, and residents did not know about coklit or even did not allow coklit activities to be carried out. The efforts made by Batam International University students are to provide socialization to the community and go directly to the field so that the community can actively participate in voting during elections. Overall, elections are the main foundation in a democratic system. Elections have an important role in ensuring public participation in politics, determining leaders who will represent the interests of the state and creating an accountable and transparent government.